Development of Computational Algorithms for Clothing Thermal Functional Simulation (Journal of Fiber Bioengineering and Informatics, 2010)
This paper focuses on the development of a multi-structural computational scheme for textile thermal engineering design, which plays an important role in translating complex mathematical models into computational algorithms and to implement computational simulation of clothing wearing system consisting of human body, clothing and external environment. In this paper, the integrated models for simulating the clothing wearing system is introduced and the descretization process of the partial differential equations involved in the mathematical models is reported. Based on the descretized equation assemblies, the multi-dimensional algorithms for computational simulation are developed for clothing thermal engineering design. Furthermore, the influence of the physical properties of clothing on the simulation results is analyzed to guide the user to design the thermal performance of clothing.
Keywords: Computational algorithms; simulation models; clothing thermal function